Perlindungan Hukum Bagi Anak Korban Kejahatan Asusila oleh Prajurit TNI: Studi Kasus: Pengadilan Militer III-12 Surabaya - Christina Tabita Sitanggang; Syamsul Fatoni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the legal protection of child victims of immoral crimes committed by TNI soldiers in Military Court III-12 Surabaya. This study focuses on the effectiveness of military law in protecting children's rights and the challenges that arise in these cases. Using a juridical-sociological legal research method, data was obtained through interviews with judges and legal counsel, as well as analysis of laws and regulations. The research findings show that the protection of children in the military context is still inadequate. The provisions of military law, especially the KUHPM, focus more on sanctioning perpetrators than on the welfare of victims. Child protection is generally regulated in Law No. 35/2014 on Child Profeatection. However, law enforcement by Military Courts remains limited. This study highlights the need to improve the military legal framework to ensure better protection for child victims, especially in cases involving TNI soldiers